IMPLEMENTASI PROJEK PENGUATAN PROFIL PELAJAR PANCASILA (P5) DI SMP N 1 WELERI - SETIYANTI, WITA; HERFIYANTI, NASYROHAH; NURKOLIS, NURKOLIS (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2024)
This research aims to determine the implementation of the Strengthening Pancasila Student Profile (P5) Project activities at SMP N 1 Weleri and its impact on students. The qualitative method with a descriptive approach is the method used. Data was collected through interviews with 2 teachers teaching classes IIV VIII and IX who had implemented the independent curriculum in learning and 5 students in classes IIV VIII and IX as participants in P5 activities. In implementing the independent curriculum, students create or implement projects. Implementation of P5 activities is one of the independent curriculum project activities. The activities carried out at SMP N 1 Weleri with the theme Bhinneka Tunggal Ika